Atrial Fibrillation Termination as a Predictor for Persistent Atrial Fibrillation Ablation: A Systemic Review and Meta-Analysis of Prospective Studies - Jialing He; Zhen Zhang; Duan Luo; Xianchen Yang; Guoshu Yang; Hanxiong Liu (Cardiovascular Therapeutics)
Conclusion: Our study establishes that AF termination serves as an effective predictor for the success of persistent AF ablation procedures. This finding holds potential implications for clinical practice and contributes to our understanding of long-term arrhythmia recurrence in the context of AF termination.